Influence of diamond rotary rolling treatment on surface integrity and fatigue resistance of 316 L stainless steel - Wenqian Zhang; Di Jiang; Peijin Zhou; Baoyi Zhu; Haishan Tang; Yijie Cai (Results in Engineering)
The fatigue performance of metal components is closely linked to surface integrity and subsurface microstructures. Thus, a novel mechanical surface strengthening method diamond rotary rolling treatment (DRRT) is proposed, which is compatible with computer numerical control (CNC) machine tools and suitable for complex geometries. This study systematically investigates the effects of DRRT on surface integrity, subsurface microstructure, and fatigue performance of 316 L stainless steel, in comparison with conventional milling. DRRT-treated surfaces exhibited significant biaxial residual compressive stress (RCS) and increased micro-hardness with greater hardened layer depth than the milled surface. DRRT refined surface grains into a gradient micro-nano structure with nanocrystalline, ultrafine, and fine grains. Compared to milling, it improved fatigue cycle life by 695 %–4555 %. Fracture analysis showed that the fatigue cracks were readily initiated on the milled surface but were absent on DRRT-treated surfaces. The improvement in fatigue resistance can be attributed to the reduced surface roughness, increased RCS, enhanced strength, and grain refinement. In addition, multi-pass DRRT processes can further improve the fatigue performance. This work provides an effective mechanical treatment method for enhancing the fatigue resistance of critical components.